Synergy of MSMEs and Food Innovation: Utilization of Raja Nangka Banana Peel Flour in Making Dry Cakes in Kalikatir Village in Kalikatir Village: Sinergi UMKM dan Inovasi Pangan: Pemanfaatan Tepung Kulit Pisang Raja Nangka dalam Pembuatan Kue Kering di Desa Kalikatir - Kurnia, Tafana Serly; Ningsih, Ika Rachman; Destiana, Evie (Proceedings of The ICECRS, 2025)
General Background: Food innovation leveraging local ingredients offers a strategic avenue for enhancing the competitiveness and sustainability of Micro, Small, and Medium Enterprises (UMKM) in the food sector. Specific Background: Kalikatir Village has untapped potential in processing agricultural waste, particularly Raja Nangka banana peels, which are rich in fiber and antioxidants, into value-added food products. Knowledge Gap: Despite the nutritional potential of banana peel waste, its application in functional food products remains limited, and there is a lack of systematic training and support for UMKM in this domain. Aims: This study aims to optimize the use of banana peel waste through comprehensive training on flour production, cookie formulation, and UMKM mentoring in production and marketing practices. Results: The initiative demonstrated that cookies made from Raja Nangka banana peel flour possess enhanced nutritional content, especially in terms of fiber and antioxidants, while maintaining consumer-acceptable taste, texture, and aroma. Novelty: This project introduces an innovative utilization of banana peel waste as a sustainable raw material, combining food innovation with capacity-building for local entrepreneurs. Implications: The activity not only promotes the diversification of local food products and reduces production costs but also strengthens UMKM skills and supports environmental sustainability. These outcomes contribute to community economic development and highlight the importance of sustainable food systems. Further research is recommended to refine product formulations and conduct market studies to support broader commercialization. Keywords: Banana Peel Flour, UMKM, Food Innovation, Sustainable Product, Kalikatir Village Highlights: Banana peel flour boosts nutrition and reduces food waste. UMKM training and mentoring improve production and marketing skills. Local food diversification drives sustainability and economic growth.